TEACHERS’ COMPETENCY AND ITS IMPLICATIONS ON TEACHERS’ RESILIENCE IN FACING SOCIETY 5.0 - Tri Achmad Efendi; Amalia Silwana (EDU RESEARCH, 2025)
This research was aimed at exploring current teachers’ competency and its implications on teachers’ readiness in facing society 5.0. As teachers play a pivotal role in helping students facing their future, it becomes mandatory for the teachers to adapt and adjust themselves with the current situation where cutting-edge technology has already influenced our lives in many ways, including education. Teachers nowadays are supposed to equip themselves with at least five competencies: digital literacy, critical thinking, adaptability, and communication. In order to find the answers, the researchers used a descriptive qualitative research design. There were two research instruments employed in this study; questionnaire and interviews. The questionnaire was distributed to thirty-two teachers and three teachers were interviewed. The results showed that of those four competencies, critical thinking is the lowest (81%) and communication is the highest (87.75%). Meanwhile digital literation and adaptability almost shares same result (around 84%). It could be inferred that the critical thinking is the area that needs improvement.